Trade-off Curves and Elasticity Analysis in Multi Fuel Options System and Combined Problem - Nazemi, Ali; Ghaderi, Seyed Farid; Khalil Moghadam, Shadi; Farsaei, Anahita (International Journal of Energy Economics and Policy, 2016)
Recent environmental concerns and policies have reformulated the traditional economic dispatch problem by including the emission impacts in the mathematical model. The combined economic and emission dispatch problem is a multi-objective non-linear optimization problem. This paper presents a method to consider the fuel costs and environmental emissions simultaneously. The -constraint method for bi-objective optimization has been used to generate Pareto front. Furthermore, trade-off curves have been developed for different types of emission. The elasticity of cost with respect to the emission (say, emission elasticity) has been estimated for all Pareto optimal points and different types of emissions that provides invaluable information for the system operator to run the system with sufficient flexibility subject to technical constraints while the operator has multi fuel options. Moreover, the emission elasticity is effective tool for competition in the electricity market. The Iranian Electricity Market is considered as empirical evidence. Keywords: Combined economic-emission dispatch, Emission elasticity, Iranian electricity market, Multi objective optimization model, Îµ-Constraint. JEL Classifications: C6, F64, P48, Q